Analysis of Community Participation through Waste Bank-Based Waste Management Using a Participatory Approach in Serang City - Af'ifah, Nikita; Jumiati, Ipah Ema; Utami, Intan Cahya; Rahayu, Diana Fitri (PUBLICUS : JURNAL ADMINISTRASI PUBLIK, 2025)
Along with the increasing population and changes in people's increasingly consumptive lifestyles, the volume of waste produced every day is increasing. The pile of waste throughout Indonesia in 2023 that is well managed is 24,266,750.68 tons/year, while waste that is not well managed is 15,850,104.69 tons/year. Banten Province is ranked fifth as the largest waste producer in Indonesia. As much as 2.6 tons/year are produced from 7 districts/cities in the region. This indicates that low public awareness of environmental cleanliness is one of the main factors causing waste accumulation. However, steps are needed to overcome the low public awareness of environmental cleanliness as the cause of this waste accumulation. The method used in this study is a literature study. Data collection through related references, ending with reading in detail and recording relevant materials to support the research analysis. This data was analyzed using a participatory approach, which aims to identify community participation, challenges faced, and the impact of policies on improving the quality of waste banks. The Waste Bank Program is an effort to reduce waste accumulation by providing incentives to the community. The Waste Bank functions not only to accommodate waste, but also to manage waste according to the needs of the community.